Language learning strategies across proficiency levels among EFL pre-university students - Ali, Hemin Hasan; Paramasivam, Shamala (Lulu Press, 2016)
Language learning strategies (LLSs) play a critical role in language learning; thus, remarkable efforts have been made to underline the significance of LLS use as well as factors influencing learners’ strategy choice. This research sought to investigate LLS use of Kurdish pre-university students learning English as a foreign language. Additionally, the researchers scrutinized the relationship between the use of language learning strategies and English proficiency. Acting in response to a call made by Oxford (1992) for additional replication of LLS research in different sociocultural contexts, this study was conducted in Kurdistan. Strategy Inventory for Language Learning (SILL), individual background questionnaire and a version of English Sunrise Test were administered to 124 Kurdish pre-university students. The findings of the study indicated that Kurdish pre-university learners were equipped with strategies of language learning at a medium level. In addition, the study revealed that metacognitive and social strategies were most preferred, whereas learners turned out to be reluctant to make use of affective strategies. The findings of the present study are in agreement with other results of prior SILL studies, showing significance between LLSs and proficiency of English in favor of advanced learners. The more advanced the learners were in the language, the greater number of strategies they applied. Level of proficiency not only had significant influence on overall strategy use but the use of all six strategy categories. The results might be advantageous in pedagogy and curriculum design. Suggestions are provided for future research concerning issues that need to be further explored.